Targeting the hard to reach: challenges and novel strategies in the treatment of intracellular bacterial infections. - Nor Fadhilah Kamaruzzaman; Kendall, Sharon; Good, Liam (The British Pharmacological Society, 2016)
Infectious diseases continue to threaten human and animal health and welfare globally, impacting millions of lives and causing substantial economic loss. The use of antibacterials has been only partially successful in reducing disease impact. Bacterial cells are inherently resilient, and the therapy challenge is increased by the development of antibacterial resistance, the formation of biofilms and the ability of certain clinically important pathogens to invade and localize within host cells. Invasion into host cells provides protection from both antibacterials and the host immune system. Poor delivery of antibacterials into host cells causes inadequate bacterial clearance, resulting in chronic and unresolved infections. In this review, we discuss the challenges associated with existing antibacterial therapies with a focus on intracellular pathogens. We consider the requirements for successful treatment of intracellular infections and novel platforms currently under development. Finally, we discuss novel strategies to improve drug penetration into host cells. As an example, we discuss our recent demonstration that the cell penetrating cationic polymer polyhexamethylene biguanide has antibacterial activity against intracellular Staphylococcus aureus.